Impact of potato processing on nutrients, phytochemicals, and human health. Issue 1 (2nd January 2018) - Furrer, Amber N.; Chegeni, Mohammad; Ferruzzi, Mario G.
ABSTRACT: Potatoes ( Solanum tuberosum ) are an important global crop that can be transformed into many products impacting several health dimensions ranging from undernutrition, food security and disease prevention to issues of overnutrition including obesity, diabetes, heart disease. Processed potato products are typically categorized as high fat and sodium foods, as well as being classified as a significant source of carbohydrate, in the form of starch. Conversely, potato products are less known for their contribution of key micronutrients (vitamin C, potassium, magnesium), fiber, and phytochemicals (phenolics and carotenoids). More recent insight into the nutritional value of potatoes and the potential of potato phytochemicals to modulate oxidative and inflammatory stress as well as the potential to alter glycemic response has resulted in increased interest in strategies to improve and leverage the nutritional quality of processed potatoes. This review summarizes critical information on nutritional profiles of potatoes and their processed products and describes the state of the science relative to the influence of in-home and common commercial processing on nutritional quality and potential impacts on human health.